2000
DOI: 10.1046/j.1471-4159.2000.0750965.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular ATP Triggers Tumor Necrosis Factor‐α Release from Rat Microglia

Abstract: Brain microglia are a major source of inflammatory cytokines, such as tumor necrosis factor-␣ (TNF-␣), which have been implicated in the progression of neurodegenerative diseases. Recently, microglia were revealed to be highly responsive to ATP, which is released from nerve terminals, activated immune cells, or damaged cells. It is not clear, however, whether released ATP can regulate TNF-␣ secretion from microglia. Here we demonstrate that ATP potently stimulates TNF-␣ release, resulting from TNF-␣ mRNA expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
336
2
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 424 publications
(362 citation statements)
references
References 47 publications
17
336
2
1
Order By: Relevance
“…Indeed, astrocytes in spinal cord, but not astrocytes isolated from various brain regions, release prostaglandins in response to substance P (Marriott et al, 1991), suggesting that spinal glia are uniquely responsive to neurotransmitters in dorsal horn. Extracellular ATP and ATP metabolites also stimulate astrocytes to release prostaglandins (Marriott et al, 1991) and microglia to release TNF (Hide et al, 2000), IL1 (Chakfe et al, 2002), and IL6 (ShigemotoMogami et al, 2001). CGRP and glutamate stimulate IL6 release as well (Kiriyama et al, 1997;Wu et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, astrocytes in spinal cord, but not astrocytes isolated from various brain regions, release prostaglandins in response to substance P (Marriott et al, 1991), suggesting that spinal glia are uniquely responsive to neurotransmitters in dorsal horn. Extracellular ATP and ATP metabolites also stimulate astrocytes to release prostaglandins (Marriott et al, 1991) and microglia to release TNF (Hide et al, 2000), IL1 (Chakfe et al, 2002), and IL6 (ShigemotoMogami et al, 2001). CGRP and glutamate stimulate IL6 release as well (Kiriyama et al, 1997;Wu et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…ATP binds to purine type 2X7 receptors (P2X7R) on nearby cells to trigger the processing and release of IL1 and TNF from glia. [53][54][55][56] Intracerebroventricular administration of an ATP agonist or ATP antagonists increases or decrease sleep, respectively. 57 P2X7R knockout animals have reduced time spent in NREMS and EEG slow wave activity after sleep deprivation.…”
Section: Atp-cytokine-adenosine Hypothesismentioning
confidence: 99%
“…We have shown previously that ATP is involved in hypoxia induced microglial activation [9]. It has been reported that on exposure to ATP, microglia exhibited changes in its electrophysiological properties [10] and increased expression of cytokines in BV2 microglial cell line as well as the primary cultured microglial cells [9,11,12]. Microglial cells are known to express P2X receptors [13].…”
Section: Introductionmentioning
confidence: 99%
“…Microglial cells are known to express P2X receptors [13]. ATP would then induce various effects through its receptors [8,11,12]. As a group of membrane cation-selective receptor channels, P2X receptors interact with extracellular ATP [13].…”
Section: Introductionmentioning
confidence: 99%